FORMATION PROBLEMS INDIVIDUAL STYLE PEDAGOGICAL COMMUNICATION FUTURE TEACHERS - H. Gribenko (Academy of Cognitive and Natural Sciences, 2022)
In the article describes essence of the democratic style of the pedagogical intercourse, and also ways of forming of the individual style of intercourse of future teachers.